Chinese Buddhism: a thematic history - Yü, Chün-fang (University of Hawaiʻi Press, 2020)
After presenting the basic tenets of the Buddha's teachings and the Chinese religious traditions, the book focuses on topics essential for understanding Chinese Buddhism: major scriptures, worship of buddhas and bodhisattvas, rituals and festivals, the monastic order, Buddhist schools such as Tiantai and Chan, Buddhism and gender, and current trends-notably humanistic Buddhism in Taiwan and the resurgence of Buddhism in post-Mao China. Each chapter ends with discussion questions and suggestions for further reading. A convenient glossary of common terms, titles, and names is included"--